2009
DOI: 10.1111/j.1750-3841.2009.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Hydroxypropylated Tapioca Starch Improves Insulin Resistance in Genetically Diabetic KKAy Mice

Abstract: The hypoglycemic and antidiabetic effect of hydroxypropyl tapioca starch (HPTS) with a varying degree of substitution (DS: 0.058, 0.091, and 0.180) was investigated in rats and KKAy mice, an animal model of type 2 diabetes. The positive incremental area under the curve (IAUC) for glucose significantly decreased as the DS of HPTS increased. The IAUC after intragastric intubation of the highest HPTS (HPTS-III, DS = 0.180) was 55% of the IAUC of tapioca starch (TS). After 28 d, fasting blood glucose and insulin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Hydroxypropylated tapioca starch retarded the development of insulin resistance in genetically diabetic KKay mice fed a normal fat diet ( 14 ) and a high-fat diet ( 15 ) . So, hydroxypropylation of HAMS would reduce the digestibility and show many physiological effects through changes of energy, glucose and lipid metabolism and fermentation.…”
mentioning
confidence: 99%
“…Hydroxypropylated tapioca starch retarded the development of insulin resistance in genetically diabetic KKay mice fed a normal fat diet ( 14 ) and a high-fat diet ( 15 ) . So, hydroxypropylation of HAMS would reduce the digestibility and show many physiological effects through changes of energy, glucose and lipid metabolism and fermentation.…”
mentioning
confidence: 99%
“…[ 24 ] Further, rats fed higher RS‐containing diets exhibited reduced serum TG levels and adipocyte size due to the low energy density of the diet. [ 14,17 ] In this study, the mean values of calorie intake during the feeding period in the PS and Ca‐PS groups were lower than those in the CON group (calorie intake [kcal per day]; CON, 45.9; HAS, 42.0; PS, 38.2; Ca‐PS, 38.5). Therefore, the lower calorie intake in the PS and Ca‐PS groups, reflected by the higher RS content, might also be one of the factors contributing to the reduced fat accumulation.…”
Section: Resultsmentioning
confidence: 57%
“…Furthermore, HP‐starch can lower digestibility both in vitro and in vivo, [ 11,12 ] and provide beneficial effects on cecal fermentation and lipid metabolism. [ 13,14 ] Therefore, the chemical modification of starch is a means of producing starches with beneficial physicochemical and physiological properties. However, evaluation of the effects of Ca‐fortified PS (Ca‐PS) on physiological properties has not been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study (Kato and others 2009), the positive incremental area under the glucose curve (IAUC) for HPTS was 55% of that for TS so the digestibility of HPTS in the small intestine was considered to be 55%. Jenkins and others (1984) have reported that there is a significant relationship between digestibility and glycemic index (IAUC of glucose response).…”
Section: Methodsmentioning
confidence: 99%